1997
DOI: 10.1159/000119383
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Effects in a Patient with Severe REM Sleep Behavior Disorder: Case Report and Theoretical Considerations

Abstract: REM sleep behavior disorder (RBD) is so far a possibly underestimated yet well-described sleep disorder. Its major impact is the vigorous sleep behavior that often results in injuries to the patient himself or to people sleeping nearby. We treated a 64-year-old male with a clinically and polysomnographically confirmed diagnosis of RBD with 3 mg melatonin, which led to a significant reduction of motor activity during sleep, as measured by actigraphy (p < 0.0001 in all analyzed movement parameters), and a full c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 6 publications
(6 reference statements)
3
50
0
1
Order By: Relevance
“…This benefit has been reported in one case report [Kunz and Bes, 1997], two open-label prospective case series of patients with RBD [Takeuchi et al 2001;Kunz and Bes, 1999] and two retrospective case series [Anderson and Shneerson, 2009;Boeve et al 2003]. Taken together, these reports include a total of 38 patients.…”
Section: Melatonin As a Therapeutic Agent In Parkinson's Diseasementioning
confidence: 80%
“…This benefit has been reported in one case report [Kunz and Bes, 1997], two open-label prospective case series of patients with RBD [Takeuchi et al 2001;Kunz and Bes, 1999] and two retrospective case series [Anderson and Shneerson, 2009;Boeve et al 2003]. Taken together, these reports include a total of 38 patients.…”
Section: Melatonin As a Therapeutic Agent In Parkinson's Diseasementioning
confidence: 80%
“…It has already been shown that cholinergic neurons in the pedunculopontine nucleus and the laterodorsal tegmental nucleus have important roles both in sleep and motor control (Garcia-Rill 1991). Kunz and Bes, in 1997, reported a 64-year-old man with severe sleep difficulties due to a rapid eye movement (REM) sleep behaviour disorder. These individuals have a loss of REM-associated atonia which results in vigorous sleep behaviour and frequently in bodily injuries.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is associated with a number of adverse reactions, especially in older patients. Beneficial effects of melatonin in the treatment of RBD were for the first time described in 1997 [5]. The aim of this article is to describe the case of a patient who received such treatment.…”
Section: Purposementioning
confidence: 99%
“…Lek ten jest jednak obarczony szeregiem działań niepożądanych, zwłaszcza w grupie pacjentów starszych. W 1997 r. po raz pierwszy opisano korzystne działanie melatoniny w terapii RBD [5]. Celem artykułu jest opisanie przypadku pacjenta, który otrzymał takie leczenie.…”
Section: Celunclassified